Adolescent Insecurity and Parental Influence - Enamhe, Dorn Cklaimz; Eba, Maxwell-Borjor Achuk (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
It requires an extraordinary intellectual exertion to be convinced about the relation of adolescent insecurity with such variables as emotional intelligence, self-concept and parental influence, there is no clear evidence regarding the exact nature of the relation in question. Insecurity is a core issue of human existence which needs special attention during adolescence and the study of factors influencing insecurity will help in developing balanced personality among adolescents. Surprisingly the study of research literature so far accomplished and accumulated in black and white shows that the realm of insecurity in adolescents has remained almost wholly untouched by earlier investigators. A diligent, cognitive incurssion into the realms of relevant international abstracts - psychological, sociological and anthropological has also brought to light that there is no clear cut empirical evidence regarding the relationship of adolescent insecurity with emotional intelligence, self-concept and parental influence. The perusal of the other related studies which have not been published so far also leads to the same conclusions. In view of this factual situation, investigations are certainly needed to discover the nature of insecurity faced by adolescents in Nigeria and also about the relationship of insecurity with relevant non organismic and organismic variables. It is the duty of the adolescent to perpetuate his race and develop some usefulness in himself as well as in others. The burden of his family, society and community lies on his shoulders. Only a secure person can perform his duty in a healthy way.